GAMBARAN FAKTOR DAN KIAT BERHENTI MEROKOK BERDASARKAN PENGALAMAN MANTAN PEROKOK AKTIF - Agustiawan Agustiawan; Sri Hajijah; Juwita Desry (Universitas Pahlawan, 2021)
Introduction: Smoking activity or behavior is one of the serious problems that can cause dangerous diseases. Methods: This qualitative study conducted in-depth interviews with three samples that we had selected based on inclusion and exclusion criteria. The inclusion criteria for the sample of this study were moderate and heavy smokers (Brinkman Index >200) and had quit smoking in the last two years. The exclusion criteria of this study were tiral smoker (trial smoker) and having comorbidities that generally make a person stop smoking due to their disease conditions. Interviews were conducted in a structured manner throughout March through the social media voice note chat application. Results: Three respondents in this study started smoking because they joined friends and quit smoking because of the increase in cigarette prices and received family support to quit smoking. Conclusion: The main principle in quitting smoking is to strengthen your intention and fill your daily life with positive activities, be it work or worship. Efforts to quit smoking are not instantaneous, so it needs support and assistance from people around someone who is about to quit smoking.